Allosteric inhibition of Staphylococcus aureus MenD by 1, 4-dihydroxy naphthoic acid: a feedback inhibition mechanism of the menaquinone biosynthesis pathway. (27th February 2023) - Stanborough, Tamsyn; Ho, Ngoc Anh Thu; Bulloch, Esther M. M.; Bashiri, Ghader; Dawes, Stephanie S.; Akazong, Etheline W.; Titterington, James; Allison, Timothy M.; Jiao, Wanting; Johnston, Jodie M.
Abstract : Menaquinones (MKs) are electron carriers in bacterial respiratory chains. In Staphylococcus aureus ( Sau ), MKs are essential for aerobic and anaerobic respiration. As MKs are redox-active, their biosynthesis likely requires tight regulation to prevent disruption of cellular redox balance. We recently found that the Mycobacterium tuberculosis MenD, the first committed enzyme of the MK biosynthesis pathway, is allosterically inhibited by the downstream metabolite 1, 4-dihydroxy-2-naphthoic acid (DHNA). To understand if this is a conserved mechanism in phylogenetically distant genera that also use MK, we investigated whether the Sau- MenD is allosterically inhibited by DHNA. Our results show that DHNA binds to and inhibits the SEPHCHC synthase activity of Sau -MenD enzymes. We identified residues in the DHNA binding pocket that are important for catalysis (Arg98, Lys283, Lys309) and inhibition (Arg98, Lys283). Furthermore, we showed that exogenous DHNA inhibits the growth of Sau, an effect that can be rescued by supplementing the growth medium with MK-4. Our results demonstrate that, despite a lack of strict conservation of the DHNA binding pocket between Mtb -MenD and Sau -MenD, feedback inhibition by DHNA is a conserved mechanism in Sau -MenD and hence the Sau MK biosynthesis pathway. These findings may have implications for the development of anti-staphylococcal agents targeting MK biosynthesis. This article is part of the theme issue 'Reactivity and mechanism in chemical and synthetic biology'.